(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2013)
In 1908, Pathé Frères faced several charges of plagiarism. Three Pathé films looked so similar to successful recent plays that some spectators easily recognized the original dramatic works. While questions concerning “adaptation” and “narrative” were central to the trial that resulted from a lawsuit brought by dramatic authors, the testimony also includes discussion of many aspects of "mise en scène," specifically about the Pathé film Cambrioleurs modernes (1907). The whole of Cambrioleurs modernes seems to have been based on the pantomime which the famous acrobat James Price (who worked on the film) had performed in Le Papa de Francine at the Théâtre Cluny in 1896. In Paris, Price had staged many “pantomimes anglaises” like this one in the style of the Hanlon-Lees, though some of them were also parts of musical plays protected by copyright after their publication. The trial that resulted from Pathé’s infringement of one such copyright thus provides rare and detailed insight into the processes by which early film studios reproduced spectacular performances by some of the most renowned stage artists.